OBITUARY : MISS ELIZABETH CARTWRIGHT - O'Dowd, Clodagh (Akroterion, 2014)
During her 38 years as Latin teacher at Rustenburg Girls' High School, Miss ElizabethCartwright gained the love and respect of the many generations of pupils who passedthrough her hands.